Angiogenesis: a target in solid tumors, also in Leukemia? - Schmidt, Thomas; Carmeliet, Peter (Hematology, 2011)
Targeting angiogenesis has become an established therapeutic approach to fighting solid tumor growth in cancer patients. Even though increased angiogenesis has long been recognized in various types of hematologic malignancies, the molecular basis underlying this angiogenic switch in leukemias remains poorly understood. The BM stroma is gaining increasing attention for its role in promoting leukemia growth and resistance against current treatments with tyrosine kinase inhibitors. This article provides a brief overview of the role of angiogenesis in leukemias, discusses recent insights into the role of placenta growth factor (PlGF), a VEGF family member, as a novel disease candidate in chronic myeloid leukemia (CML), and highlights the therapeutic potential of PlGF blockade for imatinib-resistant CML.
Gesehen am 13.10.2022